Customer loyalty - Gustavsson, Sara; Lundgren, Erica (2005)
This purpose of this thesis is to provided a deeper understanding on how companies maintain customer loyalty. This purpose is reached through two research questions focusing on and how the strategies used in maintaining customer loyalty as well as the benefits generated from customer loyalty. Theory related to each research question is reviwed, focusing more specifically on the strategies for keeping customers loyal as well as specific activities for keeping customers loyal. Theory on the benefits generated from maintaining customers loyal includes benefits for both the companies and for the customers. Data was collected via a qualitative, case study approach and focused on the use of in-depth interviweing at a Swedish retailer in Luleå, Sweden. The findings show that companies today are aware of the importance of customer loyalty by having introduced specific customer loyalty programs and for putting a lot of effort into keeping such customers loyal. Validerat; 20101217 (root)